Dynamical behaviors of a fluid-conveying curved pipe subjected to motion constraints and harmonic excitation - Lin, Wang; Qiao, Ni; Yuying, Huang (Journal of sound and vibration, 2007)
This paper investigates the nonlinear dynamics of a fluid-conveying curved pipe subjected to motion constraints and harmonic excitation. At first, the background theory for curved pipes conveying fluid with motion constraints is presented. Then, emphasis is placed on the possible nonlinear dynamic behaviors of a constrained curved pipe subject to a harmonic excitation. For such a forced dynamical system, calculations of bifurcation diagrams, phase-plane portraits, time responses, power spectrum diagrams and Poincare maps of the oscillations clearly establish the existence of the chaotic motions and quasi-periodic motions. Moreover, it is found that the route to chaos is through a sequence of period-doubling bifurcations. Finally, the difference in the nonlinear dynamics between the self-vibration system and forced system is further discussed.